Characterization of cattle production systems in Nyagatare district of Eastern province, Rwanda - Mazimpaka, Eugene (Kampala, 2016)
Unpublished dissertation (M.V. MED) - Makerere University, 2016
Includes bibliographical references (p. 50-57).
Keywords: Livestock -- Rwanda -- Nyagatare; Livestock productivity -- Rwanda -- Nyagatare